2020
DOI: 10.1002/aenm.202000335
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Macro and Atomic Structure with Elastic Properties and Ionic Transport of Glassy Li2S‐P2S5 (LPS) Solid Electrolyte for Solid‐State Li Metal Batteries

Abstract: all-solid-state batteries (ASSBs). [1] ASSBs have garnered interest since they offer the potential for improved safety and energy density compared to lithium-ion batteries. To realize these advantages, the nonflammable solid electrolyte would replace the flammable liquid electrolyte and Li metal would replace carbon anodes to reduce cell volume and weight. [2] As a result, about 100% higher energy densities could be achieved compared to conventional Li-ion batteries. [3,4] Sulfide-based electrolytes with adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 53 publications
8
58
0
Order By: Relevance
“…Similar observations of increased conductivity upon pressing were found from recent variable-pressure conductivity measurements on the isostructural Na3SbS4 44 . These observations are analogous to variations of measured ionic conductivity as a function of pellet preparation which has been reported for several solid electrolytes [64][65][66] , including ball-milled Na3PS4 56 . We attribute this to extrinsic effects on macroscopic ionic percolation through the consolidation of the pellet, improving particle-particle and pellet-electrode contact.…”
Section: Micro- Average-and Local Structures Of Ht-and Bm-na3ps4 Sysupporting
confidence: 85%
“…Similar observations of increased conductivity upon pressing were found from recent variable-pressure conductivity measurements on the isostructural Na3SbS4 44 . These observations are analogous to variations of measured ionic conductivity as a function of pellet preparation which has been reported for several solid electrolytes [64][65][66] , including ball-milled Na3PS4 56 . We attribute this to extrinsic effects on macroscopic ionic percolation through the consolidation of the pellet, improving particle-particle and pellet-electrode contact.…”
Section: Micro- Average-and Local Structures Of Ht-and Bm-na3ps4 Sysupporting
confidence: 85%
“…Subsequently, many research groups explored the composition of LPS, to elucidate the crystal structure, ionic conductivity, and fabrication of LPS-based ASSBs. Garcia-Mendez et al [219] reported the effect of molding pressure on mechanical and ionic conductivity values of LPS electrolyte, and recently, Ohno et al [220] summarized various other factors which influence the electrical properties of sulfate electrolytes.…”
Section: Lithium Phosphorus Sulfide Electrolytementioning
confidence: 99%
“…red the composition of LPS, to elucidate the crystal structure, ionic conductivity, ation of LPS-based ASSBs. Garcia-Mendez et al [219] reported the effect of molding pres echanical and ionic conductivity values of LPS electrolyte, and recently, Ohno et al arized various other factors which influence the electrical properties of sulfate electrolyte ii) Homma et al [221] studied the crystal structure and phase transitions of temperature synchrotron XRD and thermal studies were used to determine that LPS exhi phase transitions at different temperatures. The γ, β, and α phases were present at um (300−450 °C), and high (473 °C) temperature.…”
Section: Lithium Phosphorus Sulfide Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent these challenges, hot pressing can be used to consolidate sulfide-based SSE separators. [22][23][24][25][26] Hot pressing involves heating sulfide glass above its glass transition temperature so that applied pressure can effect densification through sintering and viscoplastic flow. Depending on composition, the glass transition temperature of sulfide-based SSEs ranges from about 200-350°C, which is a fraction of the temperature required to sinter oxide ceramics.…”
mentioning
confidence: 99%